The relationship between supination resistance and the kinetics and kinematics of the foot and ankle during gait - McBride, Sean; Dixon, Philippe; Mokha, Monique; Samuel Cheng, M. (Gait & posture, 2019)
•The midfoot contributes significantly to power generation during gait.•Supination resistance is related to midfoot pronation and plantarflexion moments.•Lower supination resistance is associated with greater midfoot power generation. Clinical tests of foot posture and mobility are not strongly related to the dynamic kinematics of the foot during gait. These measures may be more directly related to foot and ankle kinetics. The supination resistance test (SRT) is a clinical test that may more directly measure forces acting on the weightbearing foot to provide clinicians with insight about the loading of foot structures. What is the relationship between the SRT in relaxed calcaneal stance and in single-leg-stance and the kinetics and kinematics of the foot and ankle during gait? 10 healthy adults between the ages of 18 and 65 were recruited to participate in this study. Three-dimensional motion analysis was performed using the Oxford Foot Model during gait. The results of the SRT were compared with peak midfoot and ankle joint moments, power generation and absorption, joint angles, and peak angular velocities and accelerations. Correlation coefficients were calculated to assess the strength of relationships between these variables and the SRT. The SRT demonstrated significant relationships with several variables. In relaxed calcaneal stance, the SRT was inversely related to maximum midfoot pronation moments (r = −0.51), maximum midfoot plantarflexion moments (rho = −0.71), and peak midfoot power generation (r = −0.61). In single-leg-stance, the SRT was significantly related to maximum midfoot plantarflexion moments (rho = −0.55) and peak midfoot power generation (r = −0.47). The SRT is significantly associated to several kinetic variables that quantify midfoot loading during gait. Interventions that decrease supination resistance may have the potential to increase midfoot power generation.